The EU’s discourse coherence and its relationship with China: A new normative actor? - Alves, D. R. (SN Social Sciences, 2024)
This article examines the role of the European Union (EU) as a global actor and its relationship with China. Within the context of the current European discourse, the study delves into the EU’s role as a normative actor and the increasing challenges it faces in its interactions with China. Consequently, the article describes how, in specific facets of this relationship, the EU, through its inconsistencies in discourse, engenders a potential perception of ambivalence and vulnerability on the international stage. Therefore, the argument put forth posits that the EU’s aspiration to propagate liberal norms and principles has rendered the formulation of an appropriate foreign policy towards China difficult, as manifested by the inconsistent rhetoric employed by its highest-ranking representatives. This discord reflects the intricate task of balancing the interests of the diverse member states, thereby unveiling a fragmented EU grappling with the China predicament while attempting to sustain its normative endeavors. By employing a concept-theoretical approach, the analysis results contribute to a novel comprehension of how the EU adapts its position as a global actor in response to the adversarial nature of China, emphasizing points of discursive incongruities and interest for future research in EU-China partnerships.